Cu3ErTe3: a new promising thermoelectric material predicated by high-throughput screening. (March 2020) - Wang, T.; Xiong, Y.; Wang, Y.; Qiu, P.; Song, Q.; Zhao, K.; Yang, J.; Xiao, J.; Shi, X.; Chen, L.
Abstract: Discovering new high-performance thermoelectric (TE) materials is an eternal pursuit in TE community. Searching materials with heavy average atomic mass to realize intrinsically low lattice thermal conductivity is an effective strategy to discover novel promising TE materials. In this article, by using high-throughput screening, Cu3 ErTe3 with heavy average atomic mass is screened out of the 27, 782 entries with band gaps in the Materials Informatics Platform as a potential high-performance TE material. In experiment, a series of phase pure Cu3 ErTe3 -based samples are synthesized. Being consistent with the predication, Cu3 ErTe3 has a low speed of sound of 2151 m s −1 and an intrinsically low lattice thermal conductivity of 1.2 W m −1 K −1 at 300 K. Meanwhile, the moderate band gap of Cu3 ErTe3 enables decent electrical transport properties. Finally, a peak figure of merit around unit at 900 K is achieved for Ag-alloyed Cu3 ErTe3 . Beyond the present Cu3 Ln Te3 ( Ln = rare earth metal) compounds, other compounds predicated by the high-throughput screening, such as Cu3 La3 Bi4, Cu3 Ln 7 Te12 ( Ln = Tb, Dy, Ho, and Er), Cu2 HfTe3, and Cu3 Nd3 Sb4, might also possess excellent TE performance. This work opens a door to a large family of new potential high-performance TE materials that have not been investigated for TEs. Graphical abstract: Image 1 Highlights: Average atomic mass is used as a performance indicator for TE material high-throughput screening. Cu3 ErTe3 is selected as a case study from the screening result and synthesized in experiment. Cu3 ErTe3 has an intrinsically low lattice thermal conductivity of 1.2 W m −1 K −1 at 300 K. A peak zT around unit at 900 K is achieved for Ag-alloyed Cu3 ErTe3 .